Where are the new herbicides?. Issue 6 (2nd February 2021) - Qu, Ren‐Yu; He, Bo; Yang, Jing‐Fang; Lin, Hong‐Yan; Yang, Wen‐Chao; Wu, Qiong‐You; Li, Qing X; Yang, Guang‐Fu
Abstract: Herbicide resistance has become one of the foremost problems in crop production worldwide. New herbicides are required to manage weeds that have evolved resistance to the existing herbicides. However, relatively few herbicides with new modes of action (MOAs) have been discovered in the past two decades. Therefore, the discovery of new herbicides (i.e., new chemical classes or MOAs) remains a primary but ongoing strategy to overcome herbicide resistance and ensure crop production. In this mini‐review, starting with the inherent characteristics of the target proteins and the inhibitor structures, we propose two strategies for the rational design of new herbicides and one computational method for the risk evaluation of target mutation‐conferred herbicide resistance. The information presented here may improve the utilization of known targets and inspire the discovery of herbicides with new targets. We believe that these strategies may trigger the sustainable development of herbicides in the future. © 2021 Society of Chemical Industry Abstract : The rational molecule design strategies and precise resistance predictions in herbicide innovation will become a key to combat target mutation‐based herbicide resistance.